The complex relationship between creativity and affect - Sanchez-Ruiz, Maria-José (2014)
The cognitive components of creativity have been widely studied since the last century. However, the role of non-cognitive elements, particularly affect, has only started to be recognized and researched in the field of psychology during the last decades. This paper offers a critical review of the most relevant contributions to the study of the relationship between creativity and affect, from the preliminary research conducted within the psychoanalytic, humanistic and cognitive frameworks, to the most current lines of research regarding the relationship between creativity and emotional states and traits. We then present three integrative and heuristic models as promising initiatives in the study of such a relationship. Finally, we highlight some theoretical and practical considerations for future studies, such as a greater delimitation of conceptualizations of creativity and affect, and the domain specificity of the relationship between them.